PENILAIAN KERUSAKAN POHON AKIBAT AKTIVITAS WISATA DI BUMI PERKEMAHAN KUBU PERAHU TAMAN NASIONAL BUKIT BARISAN SELATAN (TNBBS) - Agung Adeiv Fara Fernando; Gunardi Djoko Winarno; Rahmat Safe’i; Indriyanto Indriyanto (Jurnal Hutan Tropis, 2022)
Kubu Perahu Camp Ground is the tourist destinations in the Bukit Barisan Selatan National Park (TNBBS), located in Pekon Kubu Perahu, Balik Bukit District, West Lampung Regency. This area is an intensive utilization zone as a tourist location. The number of tourist activities in Kubu Perahu area, can cause various impacts, one of the impacts that can be observed is damage to trees. The purpose of this study is to determine the status of damage to trees in Kubu Perahu Camp Ground. The study was conducted using the Forest Health Monitoring (FHM) method. The results showed there were three tree damage locations with the most damage locations, namely 29 trunk locations (code 3); type of damage to trees with the type of damage that is open wounds caused by stabbing and cutting sharp objects; with an average tree damage level of 20%. Based on the data analysis, it is known range value 2.9-4.4 belongs to Good category, there are 13 species of trees, range value 4.5-6.0 belonging to Medium category, there are no trees in this category, and range value 6.1-7.7 are classified as Bad category, there are 5 species of trees. The status of damage to trees in Kubu Perahu Camp Ground is in the category of 290 Good trees (97%), 0 medium trees (0%), and 8 trees bad (3%).